Status, Testosterone, and Human Intellectual Performance: Stereotype Threat as Status Concern - Robert A. Josephs; Mathew L. Newman; Ryan P. Brown; Jeremy M. Beer (Psychological Science, 2003)
Results from two experiments suggest that stereotype-threat effects are special cases of a more general process involving the need to maintain or enhance status. We hypothesized that situations capable of confirming a performance stereotype might represent either a threat to status or an opportunity for enhancement of status, depending on the nature of the stereotype. The positive relationship between baseline testosterone and status sensitivity led us to hypothesize that high testosterone levels in males and females would amplify existing performance expectations when gender-based math-performance stereotypes were activated. In Study 1, high-testosterone females performed poorly on a math test when a negative performance stereotype was primed. In Study 2, high-testosterone males excelled on a math test when a positive performance stereotype was primed. The moderating effect of testosterone on performance suggests that a stereotype-relevant situation is capable of conferring either a loss or a gain of status on targets of the stereotype.